Victorian Indexing Club (VIC) see Melbourne Indexers. (March 2017) - Russell, Mary; Davis, Nikki
Abstract : Professional development in the form of a monthly meeting with free professional advice, and followed by a meal at a local restaurant, along with the added benefits of a monthly newsletter and access to a reference library. This probably doesn't sound like your typical professional development program, but describes the Victorian Indexing Club (VIC), now Melbourne Indexers, a venture got under way back in 2009 by the Victorian Branch of ANZSI.